Nanocrystalline Nb coating deposited on etched sapphire substrate by plasma alloying technique. (November 2020) - Dong, Yaqian; Zhang, Yaohui; Li, Taotao; Yang, Zhao; Lin, Hongchun; Sun, Dingbang; Wang, Ruiying; Tang, Bin
Abstract: The study of Nb–Al2 O3 system can offer promising opportunities for engineering application of sapphire, with the unique connection between Nb and Al2 O3 . The nanocrystalline Nb coating on sapphire was prepared by plasma alloying technique on sapphire single crystalline substrate surfaces of (0001) substrate orientation using hydrogen-ion etching pre-treatment. The as-deposited nanocrystalline Nb coatings exits (110) texture, and companies with (220) oriented grains. TEM images shows that Nb coating has a thickness of 600–700 nm, exhibiting elongated ''column-like'' grains structure. This phenomenon can be attributed to the self-made double glow metal infiltration vacuum furnace. This technology complements the existing process system for the preparation of Nb coating, and then has potential application. Highlights: The nanocrystalline Nb coating on sapphire were prepared by self-made plasma alloying technique on sapphire. The (110) texture appeared in nanocrystalline Nb coating is analyzed by XRD and HRTEM. This technology complements the existing process system for the preparation of Nb coating.